2014
DOI: 10.3389/fcell.2014.00017
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation in neurological diseases: improving effectiveness in animal models

Abstract: Neurological diseases afflict a growing proportion of the human population. There are two reasons for this: first, the average age of the population (especially in the industrialized world) is increasing, and second, the diagnostic tools to detect these pathologies are now more sophisticated and can be used on a higher percentage of the population. In many cases, neurological disease has a pharmacological treatment which, as in the case of Alzheimer's disease, Parkinson's disease, Epilepsy, and Multiple Sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 188 publications
(211 reference statements)
0
25
0
1
Order By: Relevance
“…Among these, the delivery of M2‐promoting cytokines by genetically modified cells and viral vector–based gene therapies seem promising and can be easily investigated for their potential in acquired epilepsies. Stem cell–based approaches are a promising new strategy for a range of human conditions, and have been trialed for cell replacement and modulating the levels of neuroprotective agents . Similarly, the viral vector–mediated modulation of inflammation could be used to modulate neuroinflammation after an epileptogenic brain insult, considering that these have been observed to be safe in mediating gene therapy in neurological conditions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the delivery of M2‐promoting cytokines by genetically modified cells and viral vector–based gene therapies seem promising and can be easily investigated for their potential in acquired epilepsies. Stem cell–based approaches are a promising new strategy for a range of human conditions, and have been trialed for cell replacement and modulating the levels of neuroprotective agents . Similarly, the viral vector–mediated modulation of inflammation could be used to modulate neuroinflammation after an epileptogenic brain insult, considering that these have been observed to be safe in mediating gene therapy in neurological conditions .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular therapies, especially with stem cells of different regenerative capacities, have been trialed in neurological disorders with chronic loss of specific cell types, such as Parkinson disease and Alzheimer disease, as well as brain injury associated with ongoing neurodegeneration such as stroke and TBI. 96 Such therapies have also shown promising outcomes in epilepsy models administering the stem cells programmed to differentiate into GABAergic interneurons to counter the excessive network excitability. 97,98 Genetically modified cells have also been injected into the brain to continuously deliver different neuropeptides or other molecules with antiepileptic potential and have shown positive outcomes.…”
Section: Cellular Therapiesmentioning
confidence: 99%
“…The genetic involvement of ubiquitin carboxy terminal hydrolase L1, serine threonine kinase 1, parkin, DJ-1, α-synuclein, and leucine-rich repeat kinase 2 have been reported in the case of genetically acquired familial PD (Dauer and Przedborski, 2003). Environmental influence in conjunction with age, genetic polymorphisms and chemical exposure predispose an individual toward sporadic PD, however the complex etiology is yet to be fully understood (Adami et al, 2014). Fitzmaurice et al showed that variation in Aldehyde dehydrogenase enhances the pesticide effect related to PD thereby proving that environmental influences work in conjunction with genetics (Fitzmaurice et al, 2014).…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…Ling et al gave evidence at the genetic level by reporting that FTD-ALS and ALS patients carry similar mutated genes (Lee and Huang, 2015). Many gene mutations are responsible for causing familial ALS such as mutations in PFN1, FUS/TLS (fused in sarcoma/translocation in liposarcoma), TARDBP or TDP-43 (TAR-DNA-binding protein 43), UBQLN2, C9ORF72, SOD1 (superoxide dismutase 1), HNRNPA1, OPTN, and VCP (Adami et al, 2014). Recently a new gene named TBK1 has been discovered which plays a crucial role in inflammation & autophagy which are inherently associated with ALS pathogenesis (Cirulli et al, 2015).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…The amount of stem cells, as well as the speed of neurogenesis in the adult CNS are not sufficient for the regeneration and repair of defects that exist in neurological diseases, although shown to stimulate neurogenesis of brain tissue damage, as well as the particular hormones and neurotransmitters, but also that there is a circulating population of stem cells in the blood, that could perform supplementation of NPC of adult CNS [25]. Possible therapeutic exogenous sources of stem cells are ESCs, FSCs, ASCs and iPSCs [26][27][28].…”
Section: Neurogenesismentioning
confidence: 99%